2000
DOI: 10.1136/oem.57.12.810
|View full text |Cite
|
Sign up to set email alerts
|

Study of two cohorts of workers exposed to methyl methacrylate in acrylic sheet production

Abstract: Objectives-To study mortality among 4324 workers at two United Kingdom factories, Darwen, Lancashire and Wilton, Cleveland, producing polymethyl methacrylate (PMMA) sheet. The Darwen factory is still active, but the Wilton one was closed in 1970. Also, to investigate patterns of mortality after exposure to methyl methacrylate; in particular, mortality from colon and rectal cancer. Results-In the Darwen cohort, 622 deaths were identified and a further 700 deaths in the Wilton cohort. Mortalities for the cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…The highest occupational exposures to MMA occur during acrylic sheet manufacture and the two primary studies are retrospective cohort studies of workers engaged in the manufacture of acrylic sheet at two US (Walker et al 1991) and two UK facilities (Tomenson et al 2000). Both studies incorporated a comprehensive assessment of cumulative exposure to MMA and the cohorts include a high proportion of workers who experienced high levels of exposure during the earliest days of acrylic sheet production.…”
Section: Results and Critical Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest occupational exposures to MMA occur during acrylic sheet manufacture and the two primary studies are retrospective cohort studies of workers engaged in the manufacture of acrylic sheet at two US (Walker et al 1991) and two UK facilities (Tomenson et al 2000). Both studies incorporated a comprehensive assessment of cumulative exposure to MMA and the cohorts include a high proportion of workers who experienced high levels of exposure during the earliest days of acrylic sheet production.…”
Section: Results and Critical Reviewsmentioning
confidence: 99%
“…It concluded that there is evidence suggesting the lack of carcinogenicity of MMA in experimental animals but inadequate evidence in humans. New epidemiological information has recently become available following the publication of a cohort study of workers at two UK plants involved in the manufacture of poly methyl methacrylate (PMMA) sheet (Tomenson et al 2000). This study is of particular interest because it includes workers at one plant who were employed during the war years when exposure conditions would have been similar to those at the Bristol and Knoxville plants, although EA was never an ingredient of the acrylic sheet produced at the UK plants.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…All other studies have been retrospective, descriptive, observational studies; standardized mortality rate (SMR) studies comparing observed to expected death rates; or meta-analyses, which have simply lumped prior studies for analysis, including ones by the same authors (Table 5) [4][5][6][7][8]. The design of this study permitted the exact confirmation of professional lifetime occupations and underlying causes of death.…”
Section: Discussionmentioning
confidence: 99%
“…Most MMA carcinogenicity studies in humans have been combined retrospective cohort studies from the 1930s through the 1990s, or meta-analyses of the same and similar studies [4][5][6][7][8][9][10]. In addition, most of the negative cancer studies were authored by epidemiologists employed by major chemical manufacturers of MMA in the USA (American Cyanamid Company, Wayne, NJ; Rohm and Hass Co., Croydon, PA) and in the UK (Imperial Chemical Industries; Lucite International UK Ltd.) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%